Kandungan Asam Oksalat Sayur Bayam - Herlena Fitriani; Nurlailah Nurlailah; Dinna Rakhmina (Poltekkes Kemenkes Banjarmasin Jurusan Analis Kesehatan, 2016)
Spinach is one of vegetable that is often used as processed food by the people of Indonesia. Besides containing many nutrients, spinach also contains chemical compounds that are negative, that is oxalic acid. Oxalic acid and its salts are water soluble that can be harmful because these compounds are toxic. This study aimed to determine differences in levels of oxalic acid in spinach when the water is allowed to stand at room temperature. The type of research was pre-experiment with one group pretest-posttest design. Samples of spinach water were divided into 4 treatment and the level of oxalic acid was examined by using permanganometry titration method. Results of research on each treatment showed oxalic acid levels on 0 hour standing was 3753.2 mg/L, 2 hours standing was 3980.0 mg/L, 4 hours standing was 4066.5 mg/L, and the 6 hours standing was 4254.5 mg/L. Repeated ANOVA statistical test results stated there were significant differences in the levels of oxalic acid in spinach water between 0 hour standing and room temperature-standing with a significance value of p